PERANCANGAN SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS WEB PADA SEKOLAH MI DAARUL HIKMAH (PINK 02) - Yoraeni, Ani; ., Syafrianto; Sadiah, Alfany (JURNAL GAUNG INFORMATIKA, 2020)
Registration at a school is a very important initial process. With a good registration system will simplify and streamline the process of admission of new students. With the development of technology today, making all community activities related to the world of the internet, including in the process of accepting new students at a school. MI DAARUL HIKMAH (PINK 02) is a private elementary school based on Islamic religious education. This school has been established since 1998 with a higher public awareness of the importance of religious knowledge, causing many new students who want to enter this school. New Student Registration at this school still uses a manual system, and raises several problems. Among the differences in the existing data on the New Student Registration Committee and the Administration, there are often double data, and the process of disseminating information is less efficient to the Walimurid. An application is needed that facilitates the process of accepting new students at this school. Then the MI DAARUL HIKMAH New Student Registration Information System (PINK 02) was successfully created. The design of a web-based student registration information system can assist the school in carrying out the registration and admission of prospective new students. The entire data can be stored in a database that will be a school archive will be far safer than having to save reportsfiles that are not efficient and allow damage and loss. This information system can display announcements of new students who are accepted or rejected.